1999
DOI: 10.1038/sj.hdy.6884790
|View full text |Cite
|
Sign up to set email alerts
|

Population structure and gene flow of the Brazilian shrub Helicteres brevispira

Abstract: Helicteres brevispira is a pioneer species of the tropical riparian forest whose populations appear to cycle through episodes of extinction and recolonization. Therefore, genetic consequences of founding events may strongly a ect the genetic structure of its populations. An analysis of F-statistics showed that the studied population of H. brevispira is genetically substructured with the highest values of F ST found in areas of high plant densities. Spatial autocorrelation analysis showed that genetic patches h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
27
0
1

Year Published

2000
2000
2020
2020

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 29 publications
(29 citation statements)
references
References 32 publications
1
27
0
1
Order By: Relevance
“…As fêmeas de C. aureoventris, assim como os indivíduos de P. pretrei, no entanto, atuam como "traplining", promovendo o fluxo gênico a distâncias mais longas. Este fato favorece a coesão genética dentro de uma população (Franceschinelli & Kesseli 1999, Franceschinelli & Bawa 2000, assim como entre populações conspecíficas próximas, e também favorece o cruzamento entre espécies simpátricas. Este último caso justificaria a presença de híbridos em muitos locais de ocorrência destas espécies com outras congenéricas (Taylor 1991, Lambert et al 2006.…”
Section: Resultsunclassified
“…As fêmeas de C. aureoventris, assim como os indivíduos de P. pretrei, no entanto, atuam como "traplining", promovendo o fluxo gênico a distâncias mais longas. Este fato favorece a coesão genética dentro de uma população (Franceschinelli & Kesseli 1999, Franceschinelli & Bawa 2000, assim como entre populações conspecíficas próximas, e também favorece o cruzamento entre espécies simpátricas. Este último caso justificaria a presença de híbridos em muitos locais de ocorrência destas espécies com outras congenéricas (Taylor 1991, Lambert et al 2006.…”
Section: Resultsunclassified
“…However, some authors have argued that the difference between these two estimates gives little indication of biparental inbreeding ( Ritland, 1985; Coates & Sokolowski, 1992). There are also indications that this population is substructured ( Franceschinelli & Kesseli, 1999). Substructuring could have induced biparental inbreeding and high fixation index ( F ) in this population.…”
Section: Discussionmentioning
confidence: 99%
“…However, not many authors studied this fact from individuals perspective, evaluating genetically substructured populations. Franceschinelli and Kesseli (1999) evaluated a population of the pioneer shrub, Helicteres brevispira (Sterculiaceae) and, although they concluded that it was genetically substructured, data did not fit for isolation by distance model. However, for M. fistulifera the model seemed to fit, as Mantel test demonstrated that closer individuals were more similar genetically than distant ones.…”
Section: Discussionmentioning
confidence: 99%